STRATEGI PENGELOLAAN KAWASAN KOTA CINA, MEDAN, SUMATERA UTARA BERBASIS MASYARAKAT - , STANOV PURNAWIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kota Cina in North Sumatera Province is closely linked to Southeast Asianâs trading networks from at least 12th to 14th century. Archaeological research that have been done before is aims to prove that the region was once a tradding port, as well as settlement, throughout this period. Kota Cina region covers approximately 25 hectares, consisting of Danau Siombak, Kota Cina, Keramat Pahlawan, and Lorong IX sites. The sites are now threaten, especially by the rapid growth of population. This research is aims to arrange an appropriate strategy for managing the region which has a lot of valuable cultural heritage based on community interest. The strategy itself is oriented to preserve and utilize the heritage for public. The main concept is that management (preservation and utilization) of heritage regions cannot be separated from community who own or living at the same place. Consequently, interactions, relations and expectations of people who living there have to be considered. Observation and interview were conductedto know the expectations of these peoples. There are four strategies proposed in managing Kota Cina region. First is to set upthe site as cultural heritage region according to Indonesian Law No. 11 Year of 2010 about Cultural Heritage. Second is to establish an organization as a media for all stakeholders to share and decide steps needed to be taken in management. Third, developing tourism based on public interest is the third strategy to be offered. The last is to increase research, especially for keeping and improving the relationship betweenarchaeology and public, and concerning with cultural heritage of the region. Key words: Community, Kota Cina Regions, Cultural Heritage Management